Penyuluhan Pembuatan Tepung Kulit Pisang dan Produk Olahannya bagi Siswa Siswi SMK Negeri 1 Bawen - Aldila Sagitaning Putri; Haslina Haslina; Mita Nurul Azkia; Erwin Nofiyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
SMK Negeri 1 Bawen is located in Bawen District, Semarang Regency, and has six Expertise Programs, namely Agricultural Product Agribusiness, Plant Production Agribusiness, Livestock Production Agribusiness, Agricultural Mechanization, Food, and Tourism. Graduates of SMK Negeri 1 Bawen have spread across various regions of the archipelago and work in various sectors of the business and industrial world. This proves that SMK Negeri 1 Bawen is able to produce graduates with qualified vocational skills. This community service activity aims to provide additional knowledge to the students of SMK Negeri 1 Bawen about the importance of processing banana peels into value-added products, such as banana peel flour and cookies made from banana peels. In addition, this activity also provides information about food safety and the content of bioactive compounds in banana peels, which can be used to support health and innovation of food products. The community service program with the title